Designing solvate ionogel electrolytes with very high room-temperature conductivity and lithium transference number. Issue 47 (26th November 2018) - Hubble, Dion; Qin, Jiaxu; Lin, Francis; Murphy, Ian A.; Jang, Sei-Hum; Yang, Jihui; Jen, Alex K.-Y.
Abstract : Freestanding gel electrolytes based on Li(G4)TFSI/PEG are demonstrated with enhanced lithium transport and stripping/plating performance due to unique chemical interactions. Abstract : Free-standing electrolytes based on Li(G4)TFSI and chemically-crosslinked poly(ethylene glycol), as well as functional co-monomers and/or small amounts of volatile diluent, are demonstrated to reach very high room-temperature ionic conductivities (>2 × 10 −3 S cm −1 ) and electrochemically-measured lithium transference numbers (>0.5). An unexpected dependence of properties on polymer length/crosslinking is observed and explained in terms of competing Li + transport processes. These electrolytes enable lithium symmetric cells to cycle >600 h at low overpotential and without dendrite growth. Future optimization routes are also discussed.